2003
DOI: 10.1042/bj20030984
|View full text |Cite
|
Sign up to set email alerts
|

Proton conductance and fatty acyl composition of liver mitochondria correlates with body mass in birds

Abstract: The proton conductance of isolated liver mitochondria correlates significantly with body mass in mammals, but not in ectotherms. To establish whether the correlation in mammals is general for endotherms or mammal-specific, we measured proton conductance in mitochondria from birds, the other main group of endotherms, using birds varying in mass over a wide range (nearly 3000-fold), from 13 g zebra finches to 35 kg emus. Respiratory control ratios were higher in mitochondria from larger birds. Mitochondrial prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
97
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 35 publications
13
97
3
1
Order By: Relevance
“…As it is in mammals, the proton leak of isolated liver mitochondria is allometrically related to body mass in birds (37). The PUFA content of avian liver mitochondrial membranes is negatively related to body mass, and this was predominantly due to decreased levels of n-6 PUFA as birds increased in body mass (37). This differs from the situation in mammals where it is n-3 PUFA variation that is primarily responsible for body size trends in liver mitochondrial membrane composition (289).…”
Section: A Metabolic Rate and Body Size Of Birdscontrasting
confidence: 47%
See 2 more Smart Citations
“…As it is in mammals, the proton leak of isolated liver mitochondria is allometrically related to body mass in birds (37). The PUFA content of avian liver mitochondrial membranes is negatively related to body mass, and this was predominantly due to decreased levels of n-6 PUFA as birds increased in body mass (37). This differs from the situation in mammals where it is n-3 PUFA variation that is primarily responsible for body size trends in liver mitochondrial membrane composition (289).…”
Section: A Metabolic Rate and Body Size Of Birdscontrasting
confidence: 47%
“…As for mammals, membrane-associated processes are significant components of respiration rate of avian hepatocytes and, while the total respiration rate decreases with body mass, the relative contribution of mitochondrial ATP production, mitochondrial proton leak, and nonmitochondrial processes is unchanged (91). As it is in mammals, the proton leak of isolated liver mitochondria is allometrically related to body mass in birds (37). The PUFA content of avian liver mitochondrial membranes is negatively related to body mass, and this was predominantly due to decreased levels of n-6 PUFA as birds increased in body mass (37).…”
Section: A Metabolic Rate and Body Size Of Birdsmentioning
confidence: 90%
See 1 more Smart Citation
“…It matches a previous finding in mammals that larger species have lower densities of mitochondria per gram of liver and are longer-lived (Passos et al 2007b). Moreover, it has already been suggested that differences in mitochondria proton conductance between bird species is more likely to be explained by differences in inner-membrane properties than by variations in the amount of membranes (Brand et al 2003). Altogether, our results suggest that longer lifespan in bird species may be associated both with lower densities of mitochondria per RBC and with greater amount of cardiolipin in their mitochondrial inner membrane, which are both expected to reduce mitochondrial ROS production.…”
Section: Modelsupporting
confidence: 61%
“…Small bird species have more polyunsaturated membrane lipids than do larger birds in skeletal muscle (Hulbert et al 2002), heart (Szabo et al 2006), and liver mitochondria (Brand et al 2003), as well as kidney (A.J. Hulbert, unpublished).…”
Section: Birds Compared To Mammalsmentioning
confidence: 99%